The Status of Outside Marriage Children (The Study of Constitutional Court Regulation No. 46/PUU-VIII/2010 on February 27th, 2012 Based on the Fuqaha' Perspective) - Hamam, Hamam (International Journal of Educational Research & Social Sciences, 2021)
Fornication is a kind of jarimah (felony) resulting in confusion of the biological father. However, nowadays, there is clarity on the status of the children out of marriage. The Constitutional Court issued a decision of regulation No. 46/PUU-VIII/2010 on February 27th, 2012 about the out wedlock children who have a civil relationship and the blood rapport with their biological father as long as it can be proven biologically. This regulation drives some criticisms from various parties; the pro-side of the Court Regulation will claim it in the term of the doer of the adultery, while the contra-side of the Court Regulation will review it in the term of legalized the adultery. Furthermore, the aims of this study are: First, to know the opinion of jurists' law (fuqaha‟) about the status of the out of wedlock children; Second, to find the legal implications of the out of wedlock children after the application of the Constitutional Court regulation No. 46/PUU-VIII/2010 on February 27th, 2012 based on the Fuqaha' perspective?. Moreover, this study uses the library research. The data are collected through the documentary of the primary and secondary data sources. The collected data are, then, analyzed qualitatively by using the content analysis. The results of this study are: Firstly, This according by the Shafi'i jurists' of four and the ad-Dzahiri the out of wedlock children (bastard) are not related to their biological father, but they are related to their biological mother and her family. Secondly, This according by some groups of Hanafi and Shaykh of Islam Ibn Taymiyah corroborated by ibn Qayyim al-Jauziyyah the wedlock children (bastard) are related to the men as their biological father and their father's family. Thirdly, the Constitutional Court (MK) regulations do not have any legal implications associated on the civil relationships of the out wedlock children (natural children) with their biological father. Moreover, the attitude of the biological father is classified as a jarimah (felony), and it is entitled to a penalty of the ta'zir; it is an obligation to provide the children, which the amount is considered to the fit and proper in accordance income of his; while the other civil rights includes the right of lineage, inheritance, and the rights of guardians. The ta'zir punishments in the provision of livelihood can be executed after the filing of a lawsuit and obtain an order from the Religion Court. The provision of the living is solely to satisfy the justice and legal protection for the interests of children's rights.